Nitric Oxide-cGMP Signaling Stimulates Erythropoiesis through Multiple Lineage-Specific Transcription Factors: Clinical Implications and a Novel Target for Erythropoiesis - Ikuta, Tohru (PLoS One, 2016)
Much attention has been directed to the physiological effects of nitric oxide (NO)-cGMP signaling, but virtually nothing is known about its hematologic effects. We reported for the first time that cGMP signaling induces human γ-globin gene expression. Aiming at developing novel therapeutics for anemia, we examined here the hematologic effects of NO-cGMP signaling in vivo and in vitro. We treated wild-type mice with NO to activate soluble guanylate cyclase (sGC), a key enzyme of cGMP signaling. Compared to untreated mice, NO-treated mice had higher red blood cell counts and total hemoglobin but reduced leukocyte counts, demonstrating that when activated, NO-cGMP signaling exerts hematopoietic effects on multiple types of blood cells in vivo. We next generated mice which overexpressed rat sGC in erythroid and myeloid cells. The forced expression of sGCs activated cGMP signaling in both lineage cells. Compared with non-transgenic littermates, sGC mice exhibited hematologic changes similar to those of NO-treated mice. Consistently, a membrane-permeable cGMP enhanced the differentiation of hematopoietic progenitors toward erythroid-lineage cells but inhibited them toward myeloid-lineage cells by controlling multiple lineage-specific transcription factors. Human γ-globin gene expression was induced at low but appreciable levels in sGC mice carrying the human β-globin locus. Together, these results demonstrate that NO-cGMP signaling is capable of stimulating erythropoiesis in both in vitro and vivo settings by controlling the expression of multiple lineage-specific transcription factors, suggesting that cGMP signaling upregulates erythropoiesis at the level of gene transcription. The NO-cGMP signaling axis may constitute a novel target to stimulate erythropoiesis in vivo.